The Urgency of Intellectual Property Rights Protection in Efforts to Improve Community Welfare in South Kalimantan: Viewed from Legislation and Maqashid al-Syari'ah - Dian May Syifa; Muhammad Rangga; Mayasari; Muhammad Haris (Sharia Journal and Education Center Publishing, 2023)
Advances in information and transportation technology have occurred so rapidly that they have driven globalization in the field of intellectual property, as this requires protection of intellectual property rights. Intellectual property plays an important role in the economy of a country in realizing the welfare of a society. Through a juridical approach, this research is carried out by relying on reading materials in the form of books, scientific research journals and social realities that occur in society, so as to get answers to what is the formulation of the problem. In the context of South Kalimantan, all the efforts made by the Directorate General of Intellectual Property through its various programs, seen from 2019 until now are quite significant, and to realize the achievement of prosperity in society as the goals to be achieved in the concept of maqashid al-syariah, the role of all parties is needed. involved in the protection of intellectual property rights, including the public.